2006
DOI: 10.1186/1471-2377-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions essential for improved lexical access in an aged aphasic patient: a case report

Abstract: Background:The relationship between functional recovery after brain injury and concomitant neuroplastic changes is emphasized in recent research. In the present study we aimed to delineate brain regions essential for language performance in aphasia using functional magnetic resonance imaging and acquisition in a temporal sparse sampling procedure, which allows monitoring of overt verbal responses during scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
(37 reference statements)
2
47
0
Order By: Relevance
“…In addition, some have reported increased LH compared to RH activation after therapy (Cornelissen et al, 2003;Meinzer et al, 2004;Meinzer et al, 2007); others have found increased RH activation after therapy (Meinzer et al, 2006;Peck et al, 2004); while still others have reported bilateral activation after therapy (Fridriksson et al, 2006;Léger et al, 2002;Meinzer et al, 2007). Patterns of activation have also been reported to be more similar to controls' after therapy in one study (Léger et al, 2002), but not similar to controls' in another (Fridriksson et al, 2007).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, some have reported increased LH compared to RH activation after therapy (Cornelissen et al, 2003;Meinzer et al, 2004;Meinzer et al, 2007); others have found increased RH activation after therapy (Meinzer et al, 2006;Peck et al, 2004); while still others have reported bilateral activation after therapy (Fridriksson et al, 2006;Léger et al, 2002;Meinzer et al, 2007). Patterns of activation have also been reported to be more similar to controls' after therapy in one study (Léger et al, 2002), but not similar to controls' in another (Fridriksson et al, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…In a second study, Fridriksson et al (2007) found increased activity bilaterally in the precuneus in two nonfluent patients who responded well to a combined semantic-phonological approach to naming treatment. Meinzer and colleagues (Meinzer, Obleser, Flaisch, Eulitz, & Rockstroh, 2007;Meinzer et al, 2006;Meinzer et al, 2008) have conducted both fMRI and MEG studies to investigate neuroplastic changes on naming abilities after Constraint-Induced Aphasia Therapy (CIAT). Meinzer et al (2006) showed that correct word retrieval after treatment was associated with increased activation in the right inferior frontal gyrus (IFG) in one patient, but more bilaterally (in frontotemporal areas) in another patient (Meinzer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition, Crosson et al 35 raised the possibility that under some circumstances, activation of either the right or left hemisphere may actually interfere with rather than promote recovery of language function. Only a few studies using fMRI to monitor aphasia therapy have been published to date (eg, Wierenga et al, 39 Crosson et al, 40 Meinzer et al, 41 Peck et al, 42 Fridriksson et al, 43 and Vitali et al, 38 ), but unfortunately these studies included only small sample sizes and demonstrated divergent results regarding predominance of left-versus-right hemispheric recruitment as manifestation of posttreatment language plasticity.…”
Section: 22mentioning
confidence: 99%
“…Thus, in the last decade, the conceptualization of constraint has changed considerably, from one that was interpreted as focused solely on a response modality to one that focuses on the manner in which language action games, stimulus materials, explicit turn-taking rules, and behavioral techniques such as modeling, shaping, and positive reinforcement support overcoming learned nonuse. During this time, a growing number of investigators has replicated positive language outcomes first described by Pulvermüller et al (2001), following as little as 2 weeks of intensive therapy incorporating these three basic principles (Breier, Maher, Novak, & Papanicolaou, 2006;Kurland, Baldwin, & Tauer, 2010;Kurland, Pulvermüller, Silva, Burke, & Andrianopoulos, 2012;Maher et al, 2006;Meinzer et al, 2006Meinzer et al, , 2008.…”
mentioning
confidence: 99%